2008
DOI: 10.1007/s10533-008-9203-x
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence characteristics and biodegradability of dissolved organic matter in forest and wetland soils from coastal temperate watersheds in southeast Alaska

Abstract: Understanding how the concentration and chemical quality of dissolved organic matter (DOM) varies in soils is critical because DOM inXuences an array of biological, chemical, and physical processes. We used PARAFAC modeling of excitation-emission Xuorescence spectroscopy, speciWc UV absorbance (SUVA 254 ) and biodegradable dissolved organic carbon (BDOC) incubations to investigate the chemical quality of DOM in soil water collected from 25 cm piezometers in four diVerent wetland and forest soils: bog, forested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
282
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 370 publications
(326 citation statements)
references
References 63 publications
31
282
2
Order By: Relevance
“…In accordance with previous studies (Fellman et al, 2008), a similar share of the DOM pool in forest and mire drainage was biodegradable, indicated by the small variation in BCD-DOM across all samples (Table 1). Nonetheless, there was a large difference in the efficiency of carbon incorporation into biomass, with BGE varying fourfold ( Table 1).…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with previous studies (Fellman et al, 2008), a similar share of the DOM pool in forest and mire drainage was biodegradable, indicated by the small variation in BCD-DOM across all samples (Table 1). Nonetheless, there was a large difference in the efficiency of carbon incorporation into biomass, with BGE varying fourfold ( Table 1).…”
Section: Discussionsupporting
confidence: 92%
“…Fellman et al (2009b) showed that protein-like fluorescence decreased downstream during soil leachate additions in forested headwater streams, whereas humic-like fluorescence did not change. These observed Stedmon et al (2003).…”
Section: Incorporating Fluorescence Characterization Into Freshwatermentioning
confidence: 96%
“…Protein-like components have considerable potential for use as biogeochemical tracers, as they have been used to predict DOM lability (Fellman et al 2009a) and to fingerprint DOM derived from microbial sources (Hood et al 2009). Although protein-like fluorescence has great potential for use in a range of ecological applications, much still needs to be learned, particularly in freshwater ecosystems with high DOM concentrations, about the molecular size (Maie et al 2007) and structure of DOM that contributes to protein-like fluorescence ).…”
Section: Redox Index (Ri)mentioning
confidence: 99%
See 2 more Smart Citations